Single and Split Applications for Herbicide Efficacy in Corn - Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2024)
This study investigated the use of residual herbicides as single or sequential applications for efficacy in corn. All preemergence (PRE) herbicides provided good control of Palmer amaranth and green foxtail early in the season. Storen plus atrazine PRE and all PRE followed by postemergence (POST) treatments controlled Palmer amaranth best later in the season. Lumax EZ plus atrazine and Zidua SC plus Callisto PRE were the only treatments to provide less than 90% green foxtail control later in the year. Late-season Johnsongrass control was best with sequential applications of Acuron or Storen (90 to 96%).
Keywords: residual control